Potential for rubber(Hevea brasiliensis) cultivation on the basaltic soils of southeastern Nigeria: Climatic,pedochemical and mineralogical considerations - Eshett Ebong T; Omueti J A I (Indian Journal of Natural Rubber Research, 1989)
Three soil profiles developed on Olivine basalt, located in three villages in Ikom area of southeastern Nigeria were studied, described and characterised for the purpose of appraising their suitability for cultivation of rubber (Hevea brasiliensis) in that ecological zone. The mineralogy of clay fraction of these soils was also investigated using transmission electron microscope (TEM) and X-ray diffractometer (XRD). The soils were generally deep, moist and heavy-textured, with clay content varying from 30 to 70 per cent. Silt (2-20 mew m) content varied from 14 to 43 per cent. In spite of the clayey texture, the soils were well-drained. All the soils were strongly acidic, with moderate to high levels of soluble A1, moderate to base saturation and low ECEC. Exchangeable Ca, K and organic C were, however, appreciably high in the surface horizons. The sois had a kaolinitic clay mineralogy but there were substantial amounts of goethite, hematite, quartz and little smectite. The soils ere appraised to be suitable for rubber cultivation on the basis of the prevailing agro-climatic conditioins, excellent physical properties (texture, structure, drainage and rooting volume) and some chemical properties, mainly high organic matter, exchangeable Caand K status.
Keywords: Clay mineralogy; Hevea brasiliensis; Nigeria; Soil analysis